Mitigating Bycatch: Novel Insights to Multidisciplinary Approaches - Squires, Dale; Ballance, Lisa T.; Dagorn, Laurent; Dutton, Peter H.; Lent, Rebecca (Frontiers in Marine Science, 2021)
Fisheries bycatch conservation and management can be analysed and implemented through the biodiversity mitigation hierarchy using one of four basic approaches: (1) private solutions, including voluntary, moral suasion, and intrinsic motivation; (2) direct or “command-and-control” regulation starting from the fishery management authority down to the vessel; (3) incentive- or market-based to alter producer and consumer behaviour and decision-making; and (4) hybrid of direct and incentive-based regulation through liability laws. Lessons can be learned from terrestrial and energy conservation, water management, forestry, atmospheric pollution. General bycatch conservation and management principles emerge.